1983
DOI: 10.1128/mcb.3.4.693
|View full text |Cite
|
Sign up to set email alerts
|

In vitro nuclear transport of ribosomal ribonucleoprotein: temperature affects quantity but not quality of exported particles.

Abstract: The in vitro export of ribosomal ribonucleoprotein (rRNP) from Tetrahymena nuclei was investigated at the optimal growth temperature of 28°C and at the nonlethal temperature of 8°C. At both temperatures, nuclei exported ribosomal precursor particles that revealed the same physical qualities of size, appearance in negative-staining electron microscopy, sedimentation coefficient, buoyant density, and rRNA pattern. Surprisingly, fewer rRNP particles were exported at 8 than at 28°C, as was revealed by a lower satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Subsequent work from a number of laboratories has demonstrated that regulated RNA transport proceeds in vitro after detergent treatment (119,(123)(124)(125)(126), and hybridization properties of released poly(A)q-RNA closely resemble those of cytoplasmic poly(A)+ mRNA (126). Detergent treatment does not affect the temperature dependence of the transport process (119), which also appears to be unaffected by phase transitions of nuclear membranes (119,125), at least in mammalian systems, although somewhat different results have been obtained with Tetrahymena (127). We have found that a detergent treatment is mandatory to remove cytoplasmic contamination (see below).…”
Section: Properties Of Rna Transport In Vitromentioning
confidence: 82%
“…Subsequent work from a number of laboratories has demonstrated that regulated RNA transport proceeds in vitro after detergent treatment (119,(123)(124)(125)(126), and hybridization properties of released poly(A)q-RNA closely resemble those of cytoplasmic poly(A)+ mRNA (126). Detergent treatment does not affect the temperature dependence of the transport process (119), which also appears to be unaffected by phase transitions of nuclear membranes (119,125), at least in mammalian systems, although somewhat different results have been obtained with Tetrahymena (127). We have found that a detergent treatment is mandatory to remove cytoplasmic contamination (see below).…”
Section: Properties Of Rna Transport In Vitromentioning
confidence: 82%
“…Recently, we have shown in nuclei isolated from Tetrahyrnena Wunderlich et al, 1983) that temperature elevation from 8°C to 28"C, under export conditions, induces a gradual increase in the maximum rRNP export, i.e. the fraction of rRNP particles that can be maximally exported from nuclei gradually increases with increasing temperatures (cf.…”
Section: Discussionmentioning
confidence: 98%
“…: 50 Cihmol; NEN-chemicals, Frankfurt, F.R.G.) according to one of the procedures described in detail by Herlan et al (1980) or Wunderlich et al (1983).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations